Detection and quantification of Diaporthe destruens from soil using real-time PCR with a novel TaqMan probe - Kawabe, Masato; Erika, Sato; Yoshida, Shigenobu; Sekiguchi, Hiroyuki (Soil Microorganisms, 2025)
This study developed a TaqMan probe (TP) real-time polymerase chain reaction (qPCR) assay for the detection and quantification of Diaporthe destruens, the fungus causing sweet potato foot rot, in andosols. The primers and hybridization probe set were designed based on the ribosomal DNA internal transcribed spacer region to specifically detect D. destruens DNA, but not the similar species Diaporthe batatas. The detection limit of the novel TP assay was verified to be 0.00005 ng DNA. Along a fungal density gradient created through artificial infestation of andosols, the TP assay showed that the greater D. destruens detectability compared to those of a qPCR assay based on SYBR Green (SG) staining. In natural andosols, the TP assay demonstrated 10-fold sensitive detection of fungal DNA than the SG assay in several samples. Thus, the newly developed TP assay is more suitable for the sensitive detection and quantification of D. destruens in andosols.